Extraction of eco-friendly essential oils and their utilization in finishing polyester fabrics for fragrant and medical textiles - Mohamed M El-Molla; Ahmed H El-Ghorab (Journal of Engineered Fibers and Fabrics, 2022)
Eco-friendly fragrances essential oils of Lavender, thyme, and clove were prepared and extracted from natural sources and utilized for finishing polyester fabrics, in order to give them good smell and antibacterial characteristics, that is, medical textile. We developed medical textiles using the essential oils (lavender, thyme, and clove) with β-cyclodextrin inclusion compounds. The fragrance inclusion compounds were fixed onto polyester by drying with a low temperature and then thermo fixed method. The essential oils were studied to prove their structure using various techniques such as IR spectra, GC-MS, . . .etc. Moreover, the antibacterial activity of treated polyester fabrics with, lavender, thyme, and clove essential oils against, Staphylococcus aureus and Escherichia coli was evaluated. The results show that the finishing polyester fabrics with essential oils have antibacterial properties. The antibacterial activity of treated polyester fabrics with thyme was the highest. A strong odor was detected after 50 days, while a medium odor was detected after 60 days or five pieces of washing. The novelty of this work has arisen from its ability to fit the requirements of economic feasibility of medical textile, achieve the goal of fabrics has at smell good and has antibacterial.